Student Religiusity: Lecturers’ Experience in State Islamic University Versus State Public University - Amirah Diniaty; Salwa Mahalle; Zuriatul Khairi; Harmaini Harmaini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This study aims to document the experiences of lecturers at State Islamic Religious Colleges (PTKIN) and State Universities (PTUN) regarding student religiosity. Ten lecturers from two PTKIN and nine lecturers from two PTUN became informants for this qualitative research. In-depth interviews were conducted to collect data and analyze it narratively. The results showed that PTKIN lecturers saw that the religiosity of their students was not better than students at PTUN. It turned out that lecturers at PTUN had conducted studies on lecture material from the perspective of the Koran and encouraged their students to explore Islam through activities outside of lectures. Both lecturers at PTKIN and PTUN see that students' religiosity is formed before they go to college, and is influenced by family factors and religious extracurricular activities. The experience of lecturers at PTKIN and PTUN is that community expectations are very high for the religiosity of PTKIN students compared to PTUN students. The superior programs at PTUN need to be imitated by PTKIN such as repairing prayer facilities to increase student religiosity and activating forums for Islamic studies.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//